Dampak Perubahan Anggaran terhadap Output dan Pertumbuhan Ekonomi di Indonesia dalam Sisi Income and Spending - Carita, Herlina Reva; Hakim, Haura Khalisa; Saputra, Raden Naufal Hilmi; Fabiola, Ni Komang Mia; Albar, Izzan Shulhan; Rohman, Vanessa Azahra; Nuraya, Ahmad Setiawan (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the impact of budget changes on output and economic growth in Indonesia through the income and spending approach. Using a descriptive method that combines qualitative analysis and secondary quantitative data, this research examines data on state revenue, government expenditure, and Gross Domestic Product (GDP) from 2019 to 2024. The analysis results show that changes in budget allocation, especially during the Covid-19 pandemic, have had a significant effect on aggregate demand and the national economic performance. Although there was a decline in state revenue in 2020, increased government spending in strategic sectors successfully supported economic recovery and growth in the following years. Graphs and tables support the findings that maintaining a balance between revenue and expenditure is key to economic stability. Therefore, appropriate and adaptive fiscal policies are crucial to supporting sustainable economic growth in Indonesia.